Women and the Powers of Novel May by Sandi Firly of Michel Foucault Study - Kamariah; Tengsoe Tjahjono; Haris Supratno (LingLit Journal Scientific Journal for Linguistics and Literature, 2020)
This research examines women and power using the theory of Michel Foucault. The object of study in this research is Novel May which contains a story about a dark incident that occurred in Banjarmasin City due to political unrest. The approach used is a historical and psychological approach that analyzes the history and psychology of society with a process of individual psychological analysis. The research method used in this research is descriptive analysis method with data analysis techniques, descriptive interpretive. The results of this study indicate that (1) May's life background is divided into three parts, namely: a) May's tortuous life struggle, b) May's tremendous mental stress due to the rioting, c) sexual harassment experienced by May. (2) May's character, namely: a) the subconscious, b) the unconscious, c) the conscious mind.